SOLE 2023/28th Annual Meeting (Journal of Labor Economics, 2022)
Previous articleNext article FreeSOLE 2023/28th Annual Meeting Call for PapersPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreThe Society of Labor Economists will hold its 28th Annual Meeting on May 12–13, 2023, at the Sonesta Philadelphia Rittenhouse in Philadelphia, Pennsylvania.More details about the meeting and submission process will be available at https://www.sole-jole.org. Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 40, Number 3July 2022 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/720999 Views: 1090Total views on this site © 2022 The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.